2020
DOI: 10.1021/acschembio.0c00735
|View full text |Cite
|
Sign up to set email alerts
|

Base Pairing and Functional Insights into N3-Methylcytidine (m3C) in RNA

Abstract: N 3-methylcytidine (m3C) is present in both eukaryotic tRNA and mRNA and plays critical roles in many biological processes. We report the synthesis of the m3C phosphoramidite building block and its containing RNA oligonucleotides. The base-pairing stability and specificity studies show that the m3C modification significantly disrupts the stability of the Watson–Crick C:G pair. Further m3C decreases the base pairing discrimination between C:G and the other mismatched C:A, C:U, and C:C pairs. Our molecular dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Interestingly, the RNA duplex containing the m 3 C:G pair displays a melting temperature that is similar to those of other mismatch pairs, i.e., C:A, C:U, and C:C, indicating that this modification decreases base‐pairing discrimination and fidelity. Moreover, the results of molecular dynamics simulations are consistent with our experimental results and provide more detailed structural insights on m 3 C base pairing (Mao et al., 2020).…”
Section: Commentarysupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the RNA duplex containing the m 3 C:G pair displays a melting temperature that is similar to those of other mismatch pairs, i.e., C:A, C:U, and C:C, indicating that this modification decreases base‐pairing discrimination and fidelity. Moreover, the results of molecular dynamics simulations are consistent with our experimental results and provide more detailed structural insights on m 3 C base pairing (Mao et al., 2020).…”
Section: Commentarysupporting
confidence: 89%
“…This article reports the chemical synthesis of the m 3 C phosphoramidite building block and its incorporation into RNA oligonucleotides via solid‐phase synthesis. Its aims are to synthesize, purify, and biochemically characterize the m 3 C‐modified RNA oligonucleotide as per our recent publication (Mao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The precise function of m3C modification in tRNA remains enigmatic. However, biophysical modeling studies suggest that the m3C modification could impact tRNA structure (Mao et al 2021). To investigate a role for m3C in the folding of mt-tRNA-Ser-UGA and mt-tRNA-Thr-UGU, total RNA from WT or METTL8-KO human cells was resolved on non-denaturing native polyacrylamide gels followed by Northern blotting (Woodson and Koculi 2009).…”
Section: M3c Impacts the Conformation Of Mitochondrial Trna-ser-ugamentioning
confidence: 99%
“…For example, the spectra of methylated cytidines m 4 C, m 5 C and C m contain an ion at m/z 515, whereas this ion is absent in m 3 C (Supplementary Figure S5C). Indeed, it has been recently shown that N3 methylation, which is present on the Watson-Crick face of m 3 C, significantly weakens the base-pairing propensity of cytidine [ 35 ], which suggests that steric hindrance may prevent m 3 C dimer ( m/z 515) formation. Furthermore, similar fingerprint ionization patterns for the distinction of isomers have been characterized before using higher-energy collisional dissociation MS [ 36 ].…”
Section: Resultsmentioning
confidence: 99%